The Readiness of South Asian Countries Against Marburg Virus Outbreaks: A Perspective - Kadir, Al Kamal Muhammad Shafiul; Shemanto, Mohammad Ullah; Umar, Tungki Pratama (Bangladesh Journal of Infectious Diseases, 2024)
Marburg virus is a deadly and contagious virus that has already become an outbreak in several countries. This letter evaluates the preparedness of South Asian countries for a potential outbreak of the virus, and link it with public health framework, laboratory capacity, surveillance and response system, policy and guideline, and public awareness. It is indicated that the level of preparedness for Marburg virus and other similar diseases in South Asian countries is inadequate, with most countries lacking the necessary framework, policies, and guidelines for effective deterrence and restraint of infectious diseases. There is an urgent need for action to strengthen preparedness and response efforts in the region, including the development of comprehensive policies and guidelines, collaboration between different agencies and departments, and increased public awareness of infectious diseases. Bangladesh Journal of Infectious Diseases, June 2024;11(1):83-85